The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/obr.13205
|View full text |Cite
|
Sign up to set email alerts
|

Influence of AMY1A copy number variations on obesity and other cardiometabolic risk factors: A review of the evidence

Abstract: Summary The rising incidence of obesity and type 2 diabetes is contributing to the escalating burden of disease globally. These metabolic disorders are closely linked with diet and in particular with carbohydrate consumption; hence, it is important to understand the underlying mechanisms that influence carbohydrate metabolism. Amylase, the enzyme responsible for the digestion of starch, is coded by the genes AMY1A, AMY1B, and AMY1C (salivary amylase) and AMY2A and AMY2B (pancreatic amylase). Previous studies d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(233 reference statements)
0
3
0
Order By: Relevance
“…Amylase is secreted as salivary amylase and pancreatic amylase, of which serum amylase levels reflect both forms in roughly equal parts 81 . Regarding salivary amylase in obesity, differences in gene copy number, which may influence enzyme levels, have been the topic of ample research, but fall outside the scope of this review 82,83 . Regarding serum amylase, several studies have examined fasting levels and observed lower amylase levels with increasing adiposity 84–87 .…”
Section: Effect Of Obesity On Gastrointestinal Enzyme Secretion and S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Amylase is secreted as salivary amylase and pancreatic amylase, of which serum amylase levels reflect both forms in roughly equal parts 81 . Regarding salivary amylase in obesity, differences in gene copy number, which may influence enzyme levels, have been the topic of ample research, but fall outside the scope of this review 82,83 . Regarding serum amylase, several studies have examined fasting levels and observed lower amylase levels with increasing adiposity 84–87 .…”
Section: Effect Of Obesity On Gastrointestinal Enzyme Secretion and S...mentioning
confidence: 99%
“…81 Regarding salivary amylase in obesity, differences in gene copy number, which may influence enzyme levels, have been the topic of ample research, but fall outside the scope of this review. 82,83 Regarding serum amylase, several studies have examined fasting levels and observed lower amylase levels with increasing adiposity. [84][85][86][87] However, these results should be interpreted with caution as they could reflect changes in both pancreatic and salivary secretions.…”
Section: Pancreatic Amylasementioning
confidence: 99%
“…3a). Moreover, the selected metabolic gene set included ATP energy metabolism genes 22 (ATP2A1, ATP2C2, ATP6V0D1) located on chromosome 16, carbohydrate metabolism genes 23 (AMY1A, AMY1B, AMY1C) on chromosome 1, as well as detoxi cation and drug metabolism genes 24 (GSTM1, GSTM2, GSTM3) together (Supplementary Fig. 3b).…”
Section: Genes Functional Characteristics Of Complex Regionsmentioning
confidence: 99%